2017
DOI: 10.1091/mbc.e17-07-0450
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase SPSB4 diminishes cell repulsive responses mediated by EphB2

Abstract: Eph receptor tyrosine kinases are important for cancer development and progression as well as in cellular repulsive responses. We determined that SOCS box-containing protein SPSB4 destabilizes EphB2 cytoplasmic fragments. SPSB4 is a novel ubiquitin ligase regulating EphB2-dependent cell repulsive responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The endosomal internalisation of ephrin:Eph complexes is required for normal receptor signalling 1517 , and eventually leads to dephosphorylation of juxtamembrane tyrosines 18 , ubiquitylation of the Eph cytoplasmic tail 19 , and Eph recycling or degradation 20 . It is unknown whether the fate of internalised Eph receptors depends on the ESCRT machinery, which detects ubiquitylated receptors and transfers them between specialised vesicles, where they are sorted back to the membrane or to the lysosome 2,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The endosomal internalisation of ephrin:Eph complexes is required for normal receptor signalling 1517 , and eventually leads to dephosphorylation of juxtamembrane tyrosines 18 , ubiquitylation of the Eph cytoplasmic tail 19 , and Eph recycling or degradation 20 . It is unknown whether the fate of internalised Eph receptors depends on the ESCRT machinery, which detects ubiquitylated receptors and transfers them between specialised vesicles, where they are sorted back to the membrane or to the lysosome 2,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The SPRY domain, which more than 150 human proteins contain, was discovered as a sequence repeat responsible for protein-protein interactions [33]. The SPRY domain of SPSB proteins interacts with many cellular proteins such as Par-4, c-Met, hnRNP A1, iNOS, TβRII, SNAIL, and EphB2[2326,3436]. In this study, we first identified viral proteins HCV E1 and NS5A as those interacting with the SPRY domain of SPSB2.…”
Section: Discussionmentioning
confidence: 99%
“…SPSB3 targets SNAIL for polyubiquitination and proteasomal degradation to suppress tumor metastasis in various kinds of cancer, suggesting the vital role of SPSB3 in regulating epithelial-mesenchymal transition and cancer progression [25]. SPSB4 plays a crucial role in regulating cellular repulsive responses through interacting with and targeting EphB2 for degradation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, two studies show that EphB receptors are ubiquitylated in response to ligand binding. EphB2 is ubiquitylated by the SOCS box protein SPSB4, whose loss accentuates ephrin-B2-induced repulsive cellular responses (Okumura et al, 2017), and the ligand-induced kinase activity of EphB1 promotes its ubiquitylation by Cbl (Fasen et al, 2008). Therefore, an alternative model of HD-PTP function may involve its recruitment of deubiquitylases that counterbalance ephrin-B-induced EphB ubiquitylation, as well as promoting its recycling, since deubiquitylated Eph receptors are more likely to be recycled (Sabet et al, 2015).…”
Section: Hd-ptp: a New And Potent Effector Of Eph Signallingmentioning
confidence: 99%
“…The endosomal internalisation of ephrin:Eph receptor complexes is required for their normal signalling (Marston et al, 2003;Zimmer et al, 2003, Cowan et al, 2005, and eventually leads to dephosphorylation of juxtamembrane tyrosines (Shintani et al, 2006), ubiquitylation of the Eph cytoplasmic tail (Okumura et al, 2017) and Eph recycling or degradation (Sabet et al, 2015). It is unknown whether the fate of internalised Eph receptors depends on the ESCRT machinery, which detects ubiquitylated receptors and transfers them between specialised vesicles where they are subject to deubiquitylation, and sorting to the lysosome (Raiborg & Stenmark, 2009;Szymanska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%